Self Adaptation for Ghildren with Learning Disorders - Amitya Kumara, Amitya (2010)
Students with learning difliculties need special treatment to help them to achieve the optimum result in their study. However, their special needs are often neglected by pubtic schools, in these schools they are treated as normal childlpn. The failure to fulfill the needs of these special students will cause learning difficul- ties and low achievement. The research was ,conducted 8t som€ elementary schools which were classified by the local department of education oflice as elementary schools with the lowest rank, these schools ane located in Depok sub-distria ofSleman, Yogyakarta. The sulrjects of this study wcrc 52 students with leaming disorder. The procedures for (l) Searched information from the local office of de- tlw subject sampling 'rere: pafiment of national educalion about thc existence and information of the lowest, rank elementary school in Depok, Sleman. Yogyakarta. (2) Chose the schools that would be used as the sub.jects of thc research. (3) Used the student's learning disorder identifrcation instrument. (4) Administered the CPM intelligence test from Raven. The reeearch subjercts were comprised of 36 male students and 15 fernale stu- dents, lhe average age was I l years old. The IQ scorc (in percentile) was72.l43 for male with SD 15,,892 12.459 on the SD. Alll of the research subjects suffered from learning disorder while the fernale students' IQ score was 75.6E2 and which include: (l) genreral learning disorder 76.920/o; (2) language comprehension disorder 71.15%; (3) language expression disorder 21.15%; (4) reading disorder 75.0o/o; (5) writing disorder S0.0%; (6) ariihmetie disorder 38,46t/oi (7) orientation disorder 3.85%; (8) motor disorder 17.3lo/o; (9) attention and concentration disor- der 42.31%; (10) emottional and behavioral disorder 25.f/o and, (l l) communica- tion disorder 9.62%. The result of the sludy showed that the conhoversial nomination was thc most prevalent nomination of all with 14 students or 26.9 % showing controversial nornination, this was liollowed by 13 average students (25.00/"1, rejected stu- dents (21.27o), I neglecled studatts (15.4%), and 6 popular students (l 1.5%). The nomination comparisons among male students wer€: I I antroversial students, 8 rejected shfientq 8 avrrage stud€nts, 4 nqlected students, and 3 popular students. Whife on the female side, there were 5 average students, 4 neglecled students, 3 rejected studerrfs,3 cotilroversial students, and 3 popalar students.